(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article is dedicated to studying the role of technologies in software engineering and the field of 3D graphics, as well as exploring the problems that arise during software development. The author, drawing on her scientific experience, evaluates the use of tools such as Blender and Figma, and demonstrates new opportunities in animation and technical design. The article also examines trends in the development of this field and proposes solutions for contemporary issues.